Pengaruh Faktor Dan Variabel Makroekonomi Terhadap Hasil Investasi Pada Perusahaan Asuransi Syariah di Indonesia - ariana, yuanita dwi salfahera; Saifuddin, Saifuddin; Hamdan, Ali (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Abstract : There are many things that Indonesia has done to increase its economic growth. One way to do this is to stabilize the rate of increase in inflation and the level of investment interest, where currently many countries are trying to increase their country's economic growth rate by increasing output on an ongoing basis and what is still being discussed is the level of investment interest in the capital market. This study aims to determine the macroeconomic factors and variables that affect the investment results of sharia insurance. This research approach uses a quantitative approach to the type of associative research. The population in this study are several data sources obtained from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS) 2013-2022 years. The data analysis technique uses multiple regression analysis techniques. based on the number of samples used is purposive sampling technique, namely by taking data sources according to the criteria specified by the author on variables X (inflation, bi rate, exchange rate, money supply, Jakarta Islamic index). The use of data is taken from secondary data, namely time series data that has been published for the period 2013-2022. This research method uses a quantitative approach while the type of research is classified as associative, and uses data analysis techniques, namely multiple linear. The results of the study show that the BI Rate, Exchange Rate and Jakarta Islamic Index have a significant effect on the investment returns of Islamic insurance. On the other hand, inflation and the money supply have no significant effect.